PRESS RELEASE: SIGNIFICANT EXTEND OF POSSIBILITIES FOR REGIONAL CARDIOLOGISTS – THE MAIN TASK OF THE SECOND YEAR NATIONAL AWARD IN CARDIOLOGY “PURPLE HEART” (Рациональная фармакотерапия в кардиологии, 2016)
Press release: significant extend of possibilities for regional cardiologists – the main task of the second year National award in cardiology “Purple heart”.